THE RELEVANCE OF HUMANIST DA'WAH IN STRENGTHENING EQUALITY AND HUMAN RIGHTS IN ISLAM - Karimullah, Suud Sarim (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
This study aims to examine the relevance of humanist da'wah in the Islamic context as a solution to strengthen equality and human rights in the religious context. This study uses literature study research methods with an integrative literature analysis approach to obtain a comprehensive understanding. The results of this study stated that humanist da'wah in Islam has significant relevance in strengthening equality and human rights. Humanist da'wah, focusing on human values, justice, and compassion, opens the door to applying the principles of gender equality and human rights in the Islamic context. The role of humanist da'wah in promoting gender equality and human rights is recognized as a driving force for positive social change. However, there are still some challenges, including cultural and social issues that still support gender inequality and human rights violations, as well as technological and environmental challenges. However, there are still many important opportunities to strengthen equality and human rights, such as the role of social media and inclusive education in strengthening equality and promoting human rights awareness. Abstrak Kajian ini bertujuan untuk mengkaji relevansi dakwah humanis dalam konteks Islam sebagai solusi untuk memperkuat kesetaraan dan hak asasi manusia dalam konteks agama tersebut. Kajian ini menggunakan metode penelitian studi pustaka dengan pendekatan analisis literatur secara integratif yang bertujuan untuk mendapatkan pemahaman yang komprehensif. Hasil kajian ini menyatakan bahwa dakwah humanis dalam Islam memiliki relevansi yang signifikan dalam memperkuat kesetaraan dan hak asasi manusia. Dakwah humanis, dengan fokus pada nilai-nilai kemanusiaan, keadilan, dan kasih sayang, membuka pintu bagi penerapan prinsip-prinsip kesetaraan gender dan hak asasi manusia dalam konteks Islam. Peran dakwah humanis dalam mendorong kesetaraan gender dan hak asasi manusia diakui sebagai motor penggerak perubahan sosial positif. Namun, masih terdapat beberapa tantangan, termasuk isu-isu budaya dan sosial yang masih mendukung ketidaksetaraan gender dan pelanggaran hak asasi manusia, serta tantangan teknologi dan lingkungan. Meskipun begitu, masih ada banyak peluang penting dalam upaya memperkuat kesetaraan dan hak asasi manusia, seperti peran media sosial dan pendidikan yang inklusif dalam memperkuat kesetaraan dan mempromosikan kesadaran akan hak asasi manusia.